2017
DOI: 10.1002/app.45167
|View full text |Cite
|
Sign up to set email alerts
|

Maleic anhydride grafted linear low‐density polyethylene/waste paper powder composites with superior mechanical behavior

Abstract: The present work aims to study the perspectives of an efficient utilization of waste products as fillers for the thermoplastic polymer. Maleic anhydride grafted linear low‐density polyethylene (LLDPE‐g‐MA), without any compatibilizers, has been used as polymer matrix to prepare composites with different contents (0–50 phr) of waste paper powder (WPP). Mechanical properties assessment has shown up to 88% improvement in tensile strength and a huge increment of 409% in Young's modulus for the composites prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
1
19
1
Order By: Relevance
“…Furthermore, the concentration of stress at the particle-matrix interface region leads to weakness of the particle-matrix interaction and consequently reduces the tensile strength [ 21 ].In other words, the tensile strength is a function of the surface contact area and the interfacial strength, the modulus is a function of the surface contact area, and filler agglomeration affects both factors. However, the significant difference of the tensile modulus of samples S 0,0 and S 5,0 is not very large, but visible, while no statistically significant difference between the modulus of samples S 10,0 , S 20,0 and S 30,0 is visible.The elongation at the breaks of all composite samples, with and without compatibilizer, decreased by increasing the WGP content in the polymeric matrix, which may be explained by the fact that WGP has a high rigid stiffening effect with low deformation characteristics, which acts as a stress concentrator that increases crack initiation, and consequently, the ductility of the composite will be reduced [ 22 , 23 ].
Figure 4 The effect of WGP content on tensile strength, tensile modulus and elongation at break of RHDPE/WGP composites without compatibilizer.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the concentration of stress at the particle-matrix interface region leads to weakness of the particle-matrix interaction and consequently reduces the tensile strength [ 21 ].In other words, the tensile strength is a function of the surface contact area and the interfacial strength, the modulus is a function of the surface contact area, and filler agglomeration affects both factors. However, the significant difference of the tensile modulus of samples S 0,0 and S 5,0 is not very large, but visible, while no statistically significant difference between the modulus of samples S 10,0 , S 20,0 and S 30,0 is visible.The elongation at the breaks of all composite samples, with and without compatibilizer, decreased by increasing the WGP content in the polymeric matrix, which may be explained by the fact that WGP has a high rigid stiffening effect with low deformation characteristics, which acts as a stress concentrator that increases crack initiation, and consequently, the ductility of the composite will be reduced [ 22 , 23 ].
Figure 4 The effect of WGP content on tensile strength, tensile modulus and elongation at break of RHDPE/WGP composites without compatibilizer.
…”
Section: Resultsmentioning
confidence: 99%
“…% to achieve its maximum value at 1.5 wt. %, which may be because the addition of MAgPE increases the interfacial adhesion between the WGP particles and the RHDPE matrix, which reduces the interfacial stress concentration and reinforcement particle agglomeration [ 22 , 24 ]. On the other hand, addition of MAgPE beyond 1.5 wt.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to an extreme stiffening effect of both crosslinker, as well as CNFs, on the starch. The improvement in the elongation may be due to a uniform distribution of CNFs over the matrix, leading to better load transfer characteristics from the CNFs to the matrix and the film to absorb and dissipate the energy better upon the application of external force (Saini et al, 2017). At higher loading of CNFs and crosslinker, a high degree of entanglement and crosslink may reduce the crystallinity and increase the amorphous phase that can also contribute to the percentage of elongation (Yue et al, 2013).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…FTIR results showed that some exposed –OH groups still existed at the fiber surface after MTCS modification, indicating that the interface compatibility between hydrophobic ONP fibers and HDPE matrix was still flawed. Therefore, maleic anhydride-grafted polyethylene (MAPE), a common coupling agent used in natural fiber–plastic composites [34,35,36], was further added into the composite to improve its physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%